Standing Fast in Liberty - Stevenson, Adlai E. (Adlai Ewing) (Tufts Archival Research Center, 2006)
Adlai Stevenson, Governor of Illinois, describes his beliefs in generosity, in liberty, in the rights of man, in God's goodness and protection, in liberalism, in individualism, in freedom of conscience, in diversity and the right to dissent, and in open-mindedness. Audio also contains advertisement for "This I Believe" book.